A opção pela educação infantil bilíngue por famílias de Belo Horizonte: perfil social e motivações - João Eduardo Quadros (2013)
This study is placed in the social context of the expanding search for bilingual kindergarten schools made by socially privileged families. In order to interpret this event, I considered, as a sociological assumption, the existence of relations between the positions held by subjects in the social space and their respective education strategies. Therefore, the aims of the investigation were to trace the socioeconomic and sociocultural profile of families who choose bilingual kindergarten in Belo Horizonte and to examine the reasons that lead them to make such a decision. The participants were 28 fathers and/or mothers and 12 school professionals (teachers, coordinators and headmasters) who work at three schools that offer bilingual kindergarten in Belo Horizonte. Semi structured interviews were made in order to collect sociocultural and socioeconomic data of the participants and to inquire them about the reasons why parents choose a specific school. On the one hand, the analysis was based on a group of studies that aim to investigate the link between school choice and the different social groups. On the other hand, pieces of research about international cultural capital were also taken into account. International cultural capital is understood as the knowledge, skills and competencies which help subjects to engage confidently in international arenas. The results show that parents whose children attend two of the three schools investigated possess higher international cultural capital. These families tend to choose their school motivated by educative and/or pedagogical characteristics. The families from the other school possess lower cultural capital and they tend to choose the school mainly motivated by pragmatic reasons.